312 Metabolomics Approach to Cellular Senescence: Characterizing the Secretory Phenotype and Metabolism of Irradiation-Induced Senescent Human Pre- Adipocytes - Zinnarky Kiani Ortiz-Correa; Ian R. Lanza (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: The study aims to identify and measure metabolites in irradiation-induced senescent pre-adipocytes induced by the increased secretion of pro-inflammatory cytokines. Through untargeted metabolomics, we seek to understand the alterations to metabolism and mitochondrial activity that occur during irradiation-induced senescence. METHODS/STUDY POPULATION: First, commercially available human primary subcutaneous pre-adipocytes were cultured in vitro, and irradiated to induce senescence. To confirm senescence, cells were stained for beta-galactosidase, which was positive in senescent pre-adipocytes. The cells and their conditioned cultured media were then collected and frozen for untargeted metabolomics to profile metabolites. The sample analysis is currently underway and will be conducted using central carbon isotope tracing and chromatograph mass spectrometry. Principal Component Analysis, fold change analysis, and heat maps will be used to detect and report the changes in metabolite signals. Oxygen consumption rate and extracellular acidification rate measurements are in progress at present using the Agilent Seahorse XF Cell Mito Stress Test. RESULTS/ANTICIPATED RESULTS: We expect that metabolites of central carbon metabolism and oxidative phosphorylation will be upregulated. The concentrations of metabolites of pathways altered by the pro-inflammatory cytokines that have been identified to be secreted by senescent cells are expected to be altered. The metabolites measured in conditioned culture media will provide insight into the changes to the cellular microenvironment caused by senescence. Finally, we anticipate that mitochondrial function, and both aerobic and anaerobic metabolism will be altered in senescent pre-adipocytes compared to controls. Through the present study, we will achieve a better understanding the metabolic alterations that occur as part of cell senescence in pre-adipocytes. DISCUSSION/SIGNIFICANCE: Adipose tissue dysfunction due to the accumulation of senescent cells has been linked to chronic diseases such as diabetes and insulin resistance, and inflammaging. Through this study, we expect to provide new insight into the metabolic alterations of senescence and offer a backbone for prospective translational human studies and clinical trials.